The Utility of Smartphone 3D Scanning, Open-Sourced Computer-aided Design, and Desktop 3D Printing in the Surgical Planning of Microtia Reconstruction: a Step by Step Guide and Concept Assessment. (December 2021) - Alazzam, Abdualziz; Aljarba, Sultan; Alshomer, Feras; Alawirdhi, Bassam
Abstract: Introduction: Microtia, a congenital anomaly of the auricle with a wide spectrum of presentation with challenging reconstruction. Management depends on its severity with variable reconstructive options. Preoperative planning is crucial to achieve better results and decrease operative time. In this article, we aim to show the utility of an affordable technology with the use of a smartphone, an open-source computer-aided design (CAD) software, and a desktop 3D printer in planning future ear location for unilateral microtia reconstruction in step-by-step fashion. Methodology: Facial 3D scanning was done using a smartphone that has a three-dimensional capture system. The scan was then used in an open-sourced CAD software. A mirror image mask was created by reflecting normal side anatomic features to the abnormal side. The mask constitutes the desired area for reconstruction given the ear anthropometrics. Finally, the model was 3D printed and fitted to the patient in which incision marking and framework location was planned. Discussion: Ear reconstruction requires careful assessment and specific technicality in its anthropometric measures. One important aspect in surgical planning resides in future ear location that varies between person to person. This variability makes the reconstructive option more customized based on the patient's needs. The utility of CAD software in the measurement and planning can help predict and optimize postoperative results as possible; however, it has major technical demands and added surgical fees. Conclusion: Herein, we demonstrate the efficacy of an easy-to-use system beneficial for preoperative planning that is affordable, time-saving, and cost effective.